PUBLIC SECURITY AND PREVENTIVE MEASURES IN POLICE LAW - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2017)
Crime prevention involves activities that seek to prevent crime and offending before it occurs. It includes activities which address fear of crime. The prevention of crime requires individuals, communities, business, community organizations and all levels of government to work together. Crime prevention can reduce the long term costs associated with the criminal justice system and the costs of crime, both economic and social, and can achieve a significant return on investment in terms of savings in justice, welfare, health care, and the protection of social and human capital. A safe and secure society is an important foundation for the delivery of other key services. Community safety and security is a prerequisite for sound economic growth through continuing business investment as well as community well-being and cohesion.